DEVELOPING INSTRUCTIONAL VIDEO IN TEACHING WRITING OF RECOUNT TEXT - Diah Khofifa; Alimin Alimin; Happy Kusuma Wardani (IKIP Siliwangi, 2024)
This research focuses on the development of instructional video as a media for teaching writing recount text for the seventh graders at SMP Walisongo Sembayat. This research was conducted to provide solutions to writing teaching problems by developing appropriate, interesting, and attractive writing media that were suited to the curriculum and the needs of English teacher and students. The research applied Research and Development (R & D) by using ADDIE’s model. This model consisted of five stages; analysis, design, develop, implement, and evaluate. The subjects of this research were an English teachers and students of the seventh graders at SMP Walisongo Sembayat. The instruments for collecting the data in need analysis were questionnaires and interviews. In addition, the instruments used during the evaluation were observation checklists, field notes, teacher’s and students’ response about the media. All the data gathered through those instruments were analyzed descriptively. The final product of this research was an instructional video in the form of MP4 format. It had a size of 61.7 MB and a duration of 18 minutes 02 second. This media was developed based on Merdeka Belajar Curriculum and students' needs. It was focused on recount text materials about holiday using guided writing technique. The instructional video could increase students' motivation in learning English, especially in writing.